The Accounting-Based Prediction of Corporate Failure for Different Sectors in UK - HUANG, MIMI (2009)
The focus of this research is in the area of predicting corporate failure for different sectors in UK. It is known that the corporate failure is one of most significant threats for all the companies, no matter what are the form, size and industry of these companies. The economic costs of corporate failure are very substantial and significant for both the failed companies and the financial information users. Until now, a large number of researches were only based on US data, and didn’t consider the industry effects. However, it is believed that the industry characteristics will affect the prediction of corporate failure. Therefore, such a study is important in order to improve and enhance the understanding of the corporate failure prediction for different sectors in UK. The research method adopted in this dissertation includes an extensive review of relevant literature on corporate failure prediction, and the collection and analysis of empirical data. The latter is based on some statistical analyses of grouped financial ratios from 116 failed companies with their paired non-failed companies in four sectors in UK, developing the respective prediction models for these sectors. The findings from this research show that the corporate failure prediction models are distinguishing for these four sectors depending on their industry characteristics, and these industry-relative models can provide better predictive power than other unadjusted models. This research recommends that the industry-relative predictive model which takes into account the industry characteristics, the industry relationships and the environmental effect should be developed for each sector to achieve greater predictive power. Keywords: corporate failure, prediction, industry characteristic, industry-relative model, UK sectors.